5) (x+2)(x+3)=12
- Expand the brackets first.
- x^2 + 5x + 6 = 12
- now minus 12 from both sides to make it equal to zero
- x^2 + 5x - 6 = 0
- Factorise.
- (x+6)(x-1)=0
- x+6=0
- x-1=0
x=-6
x=1
6) (x-2)^2 = 36
- Expand.
- (x-2)(x-2)
- x^2 - 4x + 4 = 36
- Minus 36 from both sides
- x^2 - 4x - 32 = 0
- Factorise.
- (x-8)(x+4)=0
- x-8=0
- x+4=0
x=8
x=-4
8) x(x-2)=3
- Expand.
- x^2 - 2x =3
- Minus 3 from both sides.
- x^2 - 2x - 3 = 0
- Factorise.
- (x-3)(x+1)=0
- x-3=0
- x+1=0
x=3
x=-1
9)3x(x+1)=5
- Expand.
- 3x^2 + 3x = 5
- Minus 5 from both sides.
- 3x^2 + 3x - 5 = 0
- You can't factorise, so use the quadratic formula.
Your answers should come out to be:
x= 1.88(to 2 d.p.)
and
x= -0.88(to 2 d.p.)